Are Pediatric Emergency Care Applied Research Network Rules (PECARN) Sufficient for Computed Cranial Tomography Decision in Pediatric Patients with Mild Head Trauma?. Issue 1 (2016) - Durgun, Hasan Mansur; Tektaş, Erkan; Zengin, Yılmaz; Dursun, Recep; İçer, Mustafa; Üstündağ, Mehmet; Orak, Murat; Güloğlu, Cahfer
No abstract available